Plataformas nanoestructuradas de plata para identificación cualitativa de Escherichia coli mediante espectroscopia Raman intensificada por efecto de superficie “prueba de concepto del sistema” (2017)
Surface enhanced Raman spectroscopy (SERS) of nanostructured materials is a powerful technique that allows to reach ultrahigh levels of detection of several analytes. In the present study it was possible to identify the bacteria E. coli by using a novel nanostructured platform based on silver-capped nanopillars (AgNP) and SERS technique. AgNPs were fabricated by ion reactive etching and deposition of silver layers. The bacteria culture were prepared in Luria-Bertani (LB) medium at 37° by 4 hours. 5 μL of the bacteria were deposited on top of the surface of AgNPs and let it dry for 30 minutes. Subsequently the AgNP-bacteria system was analysed by Raman spectroscopy. A typical band of E. coli at 731 cm-1 was identified and this Raman vibration was used as a marker peak to detect the bacteria. Finally the novel AgNP could be used as a potential biosensor to detect nosocomial bacteria in intra-hospital environments.